2004
DOI: 10.1364/ao.43.001811
|View full text |Cite
|
Sign up to set email alerts
|

Strain mapping by measurement of the degree of polarization of photoluminescence

Abstract: A technique is described for the simultaneous measurement of the difference in the normal components of strain and of the shear strain in luminescent III-V material from the degree of polarization (DOP) of photoluminescence. This technique for the measurement of shear strain and of the difference in the normal components of strain in InP was calibrated by applying known external loads on the bars of InP with V grooves etched into the bars and by fitting the experimental results to two-dimensional finite-elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…In this notation, y points along the ͓110͔ direction, normal to the facet, z points in the ͓001͔ growth direction, x points along the facet of the bar normal to z, and C is a positive calibration constant. 10 A second, independent measurement of the DOP is obtained by rotating the polarizers 45°clock-wise about the y axis. This rotated DOP, or ROP, is defined as ROP y =2C ϫ xz , where xz is the shear strain component in the plane of interest and C is the same positive constant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this notation, y points along the ͓110͔ direction, normal to the facet, z points in the ͓001͔ growth direction, x points along the facet of the bar normal to z, and C is a positive calibration constant. 10 A second, independent measurement of the DOP is obtained by rotating the polarizers 45°clock-wise about the y axis. This rotated DOP, or ROP, is defined as ROP y =2C ϫ xz , where xz is the shear strain component in the plane of interest and C is the same positive constant.…”
Section: Methodsmentioning
confidence: 99%
“…Progress in this direction was achieved by the cross calibration of the results of known techniques, photocurrent spectroscopy ͑PCS͒, Raman spectroscopy, and microphotoluminescence. 9 In another study, degree of polarization of photoluminescence 10 ͑DOP-PL͒ and PCS have been compared. 11 In these two approaches, the techniques have been applied to single, intentionally stressed samples, which therefore experienced a strain of known symmetry, permitting successful cross calibration.…”
Section: Introductionmentioning
confidence: 99%
“…The photoresist mask was stripped with an O 2 plasma. It has been demonstrated that the DOP of PL from InP or GaAs is proportional to the difference of the strains in the material in the plane of the measured surface [9]. For measurements on the top surface,…”
mentioning
confidence: 99%
“…For InP, jK y j 65 10 [9]. L i is the measured intensity of the PL for light polarized along an i direction, i x, y, or z. ϵ xx , ϵ yy , and ϵ zz are the normal (or tensile) components of the strain tensor.…”
mentioning
confidence: 99%
See 1 more Smart Citation